Maintaining Ethical Commerce: Fiqh Perspective on Prohibiting Social Transactions in Tiktok Shop - Ahyani, Hisam; Putra, Haris Maiza; Azmi, Naelul; Syamsudin, Syamsudin; Rahman, Encep Taufik (International Journal of Islamic Economics and Governance, 2024)
This study examines the Indonesian government's efforts to curb unfair competition in cross-border e-commerce, particularly on platforms like TikTok. It evaluates these efforts through the lens of fiqh, considering Sharia compliance and economic justice. Utilizing a normative juridical approach and descriptive analytical methods, the research analyzes regulations pertaining to the prohibition of social commerce transactions involving the direct sale of foreign goods to Indonesia. Qualitative data is gathered through literature review. Findings indicate the permissibility of such measures from a fiqh perspective, justified by the concept of maslahah, which seeks to maintain market stability and protect sellers' interests. The study suggests that prohibiting social commerce transactions on TikTok fosters harmony between Sharia principles and economic fairness, promoting the preservation of various aspects of well-being. Additionally, it highlights the regulation mandating a minimum price of US$100 per unit for foreign goods sold directly to Indonesia. This regulatory provision aims to uphold fair competition and protect local markets.